Patriarchy and the (late)Victorian Middle-Class Family Reconsidered - Wojciechowska, Sylwia Janina (Horyzonty Wychowania, 2019)
RESEARCH OBJECTIVE: The aim of the article is to examine the relations within an upper middleclassfamily – as depicted by Virginia Woolf in a collection of autobiographical essays, Moments ofBeing – and compare these against the patriarchal model. The ultimate aim is to expose and locate,as early as the last decade of the Victorian era, the signs that a transformation was about to occur.THE RESEARCH PROBLEM AND METHODS: The Victorian paradigm of the patriarchal rolesof pater familias and mater familias has been analyzed. In conformity with philological methods,appropriate literary evidence is provided.THE PROCESS OF ARGUMENTATION: The article first focuses on the concept of the Victorianpater familias and mater familias. It presents an analysis of the Stephens family who feature in Momentsof Being. A traditionally conservative perspective with regard to the male family members isjuxtaposed with the contrasting viewpoint voiced by the author of the collection.RESEARCH RESULTS: The analysis of the autobiographical essays reveals certain shifts in theroles of the Victorian pater familias and mater familias in late-Victorian times. Furthermore, certainrifts in familial relations are uncovered and investigated with reference to differing attitudes to theissue of female education.CONCLUSIONS, INNOVATIONS, AND RECOMMENDATIONS: The analysis exposed severalfissures in the patriarchal model and located these at an earlier date than commonly accepted. Italso demonstrated that the first signs of the transformations that would occur in British society wereparticularly noticeable in the novel attitudes to the question of female education. This may encouragefurther research of contemporary perspectives on institutional instruction.